LncRNA GAS5 as miR-26a-5p Sponge Regulates the PTEN/PI3K/Akt Axis and Affects Extracellular Matrix Synthesis in Degenerative Nucleus Pulposus Cells in vitro - Tan, Liang; Xie, Yifang; Yuan, Ye; Hu, Kai (Frontiers in Neurology, 2021)
The role of lncRNA growth arrest specific 5 (GAS5) in degenerative nucleus pulposus cell (NPC) apoptosis has been reported, but the mechanism of GAS5 in extracellular matrix (ECM) synthesis in intervertebral disc degeneration (IDD) remains unknown. We aimed to investigate the mechanism of GAS5 in ECM synthesis in degenerative NPCs. GAS5 expression was measured in degenerative NPCs (CP-H170) and normal NPCs (CP-H097). SiRNA-mediated GAS5 knockdown was transfected to NPCs to detect cell viability and the expression of ECM-related genes (Collagen II, aggrecan, Collagen I, MMP-3). Subcellular localization of GAS5 was analyzed. The downstream gene and pathway of GAS5 in degenerative NPCs were explored. As our results indicated, lncRNA GAS5 was upregulated in degenerative NPCs. Silencing GAS5 improved the viability of degenerative NPCs and increased ECM synthesis. GAS5 was mainly located in the cytoplasm of NPCs. LncRNA GAS5 sponged miR-26a-5p to regulate PTEN. Overexpression of miR-26a-5p promoted ECM synthesis in degenerative NPCs. Akt inhibitor LY294002 reversed the promotion of silencing GAS5 on ECM synthesis of degenerative NPCs. In conclusion, lncRNA GAS5 sponged miR-26a-5p to upregulate PTEN and inhibit the PI3K/Akt pathway, thus inhibiting ECM synthesis of degenerative NPCs.